2006
DOI: 10.1007/s10973-005-7154-1
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in the β–α phase transition in silver iodide

Abstract: IntroductionSilver iodide can exist in three crystal polymorphs at atmospheric pressure [1]. Below 147°C the b-phase is stable; this has a wurtzite structure with the iodide ions arranged in a hexagonal close packed structure and with the silver ions occupying a sublattice of interstitial tetrahedral sites. Above 147°C silver iodide undergoes a crystalline transition to the high temperature a-phase, which has a body centred cubic arrangement of iodine ions with the silver ions distributed over a sublattice of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…The β polymorph has iodine anions in a hexagonal-close-packed structure 27 , 29 , 35 , the γ polymorph has iodine anions in a cubic-close-packed structure 27 , 36 , 37 . The interstitial silver cations in γ-AgI and β-AgI are relatively ordered, whereas in α-AgI they are disordered across a fraction of the tetrahedral interstices, such that the entropy difference |Δ S 0 | = 63 ± 4 J K −1 kg −1 for the α ↔ β + γ transition is large 38 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The β polymorph has iodine anions in a hexagonal-close-packed structure 27 , 29 , 35 , the γ polymorph has iodine anions in a cubic-close-packed structure 27 , 36 , 37 . The interstitial silver cations in γ-AgI and β-AgI are relatively ordered, whereas in α-AgI they are disordered across a fraction of the tetrahedral interstices, such that the entropy difference |Δ S 0 | = 63 ± 4 J K −1 kg −1 for the α ↔ β + γ transition is large 38 40 .…”
Section: Introductionmentioning
confidence: 99%
“…28 Furthermore, because ␣-silver iodide couples very strongly with a the microwave field, it proved very difficult to cool specimens from this state using the compressed air supply in the presence of microwaves. However, studies on the structural transition in silver iodide by conventional thermal analysis techniques showed that the phase change exhibited hysteresis in that transformation is not perfectly reversible.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Bulk (AgI) x ‐(Ag 2 O) 25 ‐(MoO 3 ) 75− x , for 60 ≤ x ≤ 40, vitreous solids have been prepared by microwave melting metal plate quenching method. The fundamental idea behind AgI‐based solid electrolytes with high ionic conductivity at room temperature is to hinder the α → β phase transition at lower temperatures, by introducing stabilizer ions into the lattice, that is, preserving the α‐AgI at a much lower temperature, in other words, a lower phase transition temperature . This can be efficiently achieved by microwave irradiation technique, the β—α phase transition occurs at around 100°C in this case .…”
Section: Methodsmentioning
confidence: 99%
“…The fundamental idea behind AgI‐based solid electrolytes with high ionic conductivity at room temperature is to hinder the α → β phase transition at lower temperatures, by introducing stabilizer ions into the lattice, that is, preserving the α‐AgI at a much lower temperature, in other words, a lower phase transition temperature . This can be efficiently achieved by microwave irradiation technique, the β—α phase transition occurs at around 100°C in this case . The microwave energy interacts with the crystal via phonon coupling and the low‐lying transverse optic (TO) modes dominate; Ag + mostly moves in these low energy modes that leads to Frenkel defects in the structure, allowing ionic conduction …”
Section: Methodsmentioning
confidence: 99%